Effect of sowing time and planting space on change of yield and protein content of white lupine (Lupinus albus L.) - Tóth, Gabriella (Acta Agraria Debreceniensis, 2016)
The hinge of the lupine crop cultivation technology is the sowing time and the determination of the breeding area. According to the literature the early sowing (as soon as possible to go to the soil) and larger growing area is recommended for seed production. Based on the results of our 2 years experiment, the effect of sowing time and different spacing is important on yield of white lupine, and the effect of the sowing time is more significant. A decrease in the yield was observed after later sowings. The yield and the rate of its decreasing was varied in one year and among different years depending on wheather condition and sowing time. The role of sowing time is significant for protein content of seeds. The average protein content decreased due to the later sowings in 2014, while 2015 the protein content of seeds in early sowing time and of plants sowed 4 weeks later was similar. We measured less protein content in the 2. sowing time sowed 2 weeks later than the first one. In the studied years the average protein content of seeds from different row spaces were not different.